Lil Hardin Armstrong’s Secret Ambition: Unravelling the Mystery of Mrs. Louis Armstrong’s All-Girl Orchestra - Lindhorst, Jonathan (Journal of Jazz Studies, 2026)
In the rich and complex history of women in jazz, Lil Hardin Armstrong’s All-Girl Orchestra, sometimes referred to as either the Harlem Harlicans or the Chicago Creolians, stands out as being particularly mysterious. Often referenced but never discussed in any detail, accounts of Hardin’s group are limited, usually vague, and often possess glaring inconsistencies, including the years that the band was active, conflicting accounts of the band’s activities, and even disagreement on the name of the group itself. However, through detailed archival research, a rich and comprehensive story can be pieced together that not only provides missing specifics, such as the band’s personnel, tour dates, and business dealings, but also offers insights into Hardin’s motivations for leading the group and the obstacles she encountered. Fuelled by a desire to adopt the modern compositional and arranging techniques of the emerging swing movement and managed in close collaboration with bassist/cellist Olivia Shipp and violinist Mae Brady, Hardin and her All-Girl Orchestra serves as a flashpoint in early jazz history, not just for female-driven entrepreneurship, but of pioneering creativity and an inter-generational mentorship that had a far-reaching impact on the early development of the African-American ‘all-girl’ swing band movement of the 1930s and 40s.